การประเมินศักยภาพการพัฒนาของจังหวัดแพร่ - อังยุรีกุล, นงนุช; ธรรมธนากูล, ณิธิชา; ผาสุก, สุวพร (Asian Journal of Applied Economics, 2013)
บทคัดย่อ การศึกษานี้ประเมินความสามารถหลักและกำหนดตำแหน่งยุทธศาสตร์การพัฒนาจังหวัด โดยใช้ข้อมูลทุติยภูมิวิเคราะห์ปัจจัยที่มีอิทธิพลต่อผลิตภัณฑ์มวลรวมของจังหวัด วิเคราะห์แนวโน้ม หาค่า LQ และสร้าง BCG matrix และใช้ข้อมูลปฐมภูมิจากการสัมภาษณ์ตัวอย่าง 406 ราย เพื่อวิเคราะห์แบบจำลอง TERMS วิเคราะห์ SWOT แบบจำลอง five forces แบบจำลอง general electric และ TOWS matrix ตลอดจนประเมินศักยภาพของทุน 5 ด้าน คือ ทุนทางธรรมชาติ เศรษฐกิจ มนุษย์ สังคม และการเงิน ทั้งนี้พบว่า จังหวัดแพร่มีศักยภาพในทุกสาขา แต่ควรมีการลงทุนเพิ่มเพื่อขยายโอกาสและความสามารถการแข่งขันเชิงธุรกิจ และควรเริ่มเตรียมการศึกษาทางเลือกและความเป็นไปได้ในการพัฒนาศักยภาพบนความสามารถหลักหากมีแนวคิดที่จะพัฒนาจังหวัดเป็นเมืองบริวารของกลุ่มล้านนา เพื่อเป็นศูนย์ขนส่งสินค้าสู่ประตูการค้า คำสำคัญ : การวิเคราะห์ความสามารถหลัก, จังหวัดแพร่ Abstract This study evaluates the core competency and suggests a strategy position for the development inPhrae province. The study uses secondary data to analyze factors effecting Phrae's gross provincialproduct (GPP). The analytical methods include trend analysis, latent quotient method (LQ) andBoston consulting group (BCG) matrix. The primary data was obtained from the interview of 406samples. The data was used for the analysis of TERMS model, SWOT analysis, five forces model,general electric model, TOWS matrix, and the potential evaluation of the natural, economic, human,social, and financial capitals. It is found that Phrae province has the development potential in allsectors, but requires more investment in order to increase the opportunities and its competitivenessin business. A feasibility study is suggested of alternatives and development potential based on the provincial core competency, if the province plans to become a transportation center and gateway ofLanna (the cluster of provinces in the upper north of Thailand). Keywords : core competency analysis, Phrae province